Effect of Fast Freezing with Liquid Nitrogen on Quality of Kelulut (stingless bee) Honey - Mohamad Fuzi, Siti Fatimah Zaharah; Zamri, Muhammad Irfan; Basri, Hatijah; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2021)
Kelulut honey is a highly saturated sugar solution produced by the enxymatic conversion of nectar produced by the enzymatic conversion of nectar or plant secretion. Kelulut honey contained around 80 to 85 % carbohydrates, 15 to 17 % water, 0.3 % proteins and 0.2 % ashes. Kelulut honey undergo rapid alcoholic fermentation after harvested due to its high moisture content and the presence of osmophilic yeast. This problem causes deterioration effect of honey products. Hence, liquid nitrogen was used in this study to preserve the quality of kelulut honey in term of protein content, enzyme and antioxidant compound. However, the effectiveness of liquid nitrogen in preserving kelulut honey was questionable. Therefore, this study aims to partially characterize the protein content, diastase activity and antioxidant properties of kelulut honey after freezing with liquid nitrogen. For identification of protein content, Fourier-transform infrared spectrometer (FTIR) was used to detect amide groups present in the frozen kelulut honey. Apart from that, DPPH assay was conducted to determine the radical scavenging activity while diastase assay was adopted to identify diastase activity in frozen kelulut honey using T60 UV-vis spectrophotometer. This study found that protein content, diastase activity and antioxidant properties of frozen kelulut honey were 4.6 %, 3.364 schade units and 85.12 % respectively while raw kelulut honey were 4 %, 2.884 schade units and 84.18 % respectively. This study revealed that protein content, diastase activity and antioxidant properties of frozen kelulut honey were higher than raw kelulut honey. Based on the results obtained, it can be concluded that liquid nitrogen can be used as freezing method for preserving the quality of kelulut honey.